2017
DOI: 10.1093/neuros/nyx588
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Cerebral Aneurysm From Metastatic Nonsmall Cell Lung Carcinoma: Case Report and Literature Review

Abstract: Intracranial neoplastic cerebral aneurysms are extremely rare entities, and a rare cause of subarachnoid hemorrhage. This diagnosis should be considered in patients who present with concurrent metastatic cancer and cerebral aneurysm or aneurysmal subarachnoid hemorrhage. Early initiation of chemotherapy may be beneficial in reducing the risk of tumor-particle embolization, but more research needs to be conducted to better understand this rare phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Nussbaum et al reported a case of multiple new intracranial aneurysms 4 months after treatment for an NCA due to breast cancer, 3 ) whereas Omofoye et al reported a case of SAH due to a ruptured de novo left superior cerebellar aneurysm not found on magnetic resonance angiography 19 days earlier in a patient with non-small cell lung cancer. 7 ) Moreover, the present case had a short development time of 33 days, demonstrating the possibility of aneurysm formation and rupture in a short time in NCAs associated with malignancy. In the present case, a minor leak of the SAH was observed at the routine follow-up CT on day 30, but the CTA did not include the parietal area, and the aneurysm could not be detected at that time.…”
Section: Discussionmentioning
confidence: 50%
“…Nussbaum et al reported a case of multiple new intracranial aneurysms 4 months after treatment for an NCA due to breast cancer, 3 ) whereas Omofoye et al reported a case of SAH due to a ruptured de novo left superior cerebellar aneurysm not found on magnetic resonance angiography 19 days earlier in a patient with non-small cell lung cancer. 7 ) Moreover, the present case had a short development time of 33 days, demonstrating the possibility of aneurysm formation and rupture in a short time in NCAs associated with malignancy. In the present case, a minor leak of the SAH was observed at the routine follow-up CT on day 30, but the CTA did not include the parietal area, and the aneurysm could not be detected at that time.…”
Section: Discussionmentioning
confidence: 50%
“…It is reported that the biological features of the primary tumour are involved in the development and prognosis of the aneurysm; in particular, it seems that the diffusion of tumour cells to the brain can damage vessel walls promoting aneurysm formation. In addition, it is assumed that the gravity of damage depends on the grade of malignancy of the neoplastic cells: data reports that IAs associated with benign tumours are less prone to rupture and cause intracranial haemorrhage than IAs associated with malign tumours [9][10][11]. Neoplastic IAs are mainly associated with metastatic cardiac myxomas and choriocarcinoma, and less frequently with other metastatic tumours such as lymphoma, cardiac myxosarcoma and lung cancer [9,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic etiology of intracranial cerebral aneurysm formation is rare 1,2 . Yet, some authors indicate that the risk of its development is higher in malignant tumor patients who receive radiation therapy (RT), particularly in those with a history of high radiation dose exposure to intracranial vessels 3 .…”
Section: Introductionmentioning
confidence: 99%